Genetic divergence in hyacinth bean (Dolichos lablab) - NANDI, A; TRIPATHY, P; LENKA, D (The Indian Journal of Agricultural Sciences, 2013)
A study conducted during 1994-95 to analyse the genetic diversity using Mahalanobis D2 statistic was carried outin 28 genotypes of hyacinth bean (Dolichos lablab L.). These genotypes were grouped into 5 clusters, Cluster I had 22genotypes. The analysis further indicated that the genotypes of common geographic origin or same location were groupedinto different clusters which suggested a lack of relationship between genetic and geographic diversity, The averageintercluster D2 values indicated maximum statistical divergence between cluster II and V followed by I and V and I andIV, Cluster V recorded highest mean pod length, pod weight, seeds/pod and green pod yield/plant. The first 2 canonicalvectors accountcd for 73,09% of total genetic variation.